ANALISIS OIL MONITORING SEBAGAI BAGIAN PREDICTIVE MAINTENANCE UNTUK UJI KESIAPAN OPERASIONAL BIG DIGGER KOMATSU - Taufiq, Ahmad; Finahari, Nurida; Fuhaid, Naif (ROTOR, 2014)
The performances of the equipments are measured by overall equipment effectiveness (OEE). This parameter consists of availability, operation reliability and product quality. Predictive maintenance system focus on measuring the effectiveness and availability of the vehicles used in the production process. The maintenance system usually done its work by analysis the lubrication oil used in parts of the vehicles. The parameters that will be analyzed are commonly consist of two testing procedures. The first is identify the state of lubrication performance, and the second is measuring the viscosity values of oil samples. This study try to developt the further test for the oil samples in the form of analyze the metal concentration consisted in. This procedure is meant to show the rate of part wearing as the basic of concluding the PM process. The alternative method offer maintenance cost optimation by avoiding the sudden breakdownÂ and prolong the part lifetime. The study is taking two type Big Digger Machine as comparator. The results show that the common PM has conclusion to let the PC 2000 stay in the process meanwhile the PC 4000 facing the overhaul and replacing the spareparts. The metal inclusion testing procedure show that the PC 2000 oil samples have higher metal concentration. It means that the PC 2000 parts need replacement more than PC 4000. The PC 4000 just need the overhaul process. This finding approve that alternative PM give more accurate results than the common. Keywords: oil monitoring, predictive maintenance, metal inclusion testing, big digger engine